THE EFFECT OF SEMANTIC MAPPING STRATEGY ON STUDENTS’ READING COMPREHENSION AT THE NINTH GRADE STUDENTS OF SMP RAKSANA MEDAN - Situmorang, Resniaty (Kairos English Language Teaching Journal, 2017)
This research is aimed to investigate the effect of semantic mapping strategy on studentsâ€™ reading comprehension of narrative text and the significant different on reading comprehension of narrative text between two groups: who are teach using semantic mapping strategy and those who are teach using conventional method. The design of the study is experimental study. The population of this study is the ninth grade students of SMP Raksana Medan in the academic year of 2014/2015. The number of the subjects is 60 students. The data are obtained by administering reading test to the IX-1 as experimental group and IX-2 as control group. The research is started by giving pre-test, treatment and post-test to both experimental and control groups. The data of the test are analyzed by usingÂ t-test formula to know the difference of the studentsâ€™ comprehension in reading narrativeÂ text between two groups. In the pre-test the mean score of the experimental group is 54 andÂ the control group is 53.67. The result of post-test of the experimental group is 78.33 andÂ the control group is 67.5. The result of the t-test of mean difference is 3.046 and t- table isÂ 2.00 It means that t-value is higher than t-table (3.046 >2.00). The calculation revealed thatÂ the hypothesis about a significant difference on reading comprehension between studentsÂ who are teach narrative text by using semantic mapping strategy and those who are taughtÂ by using conventional method is accepted. It can be concluded that Semantic MappingÂ Strategy worked effectively to help students increase their achievement in readingÂ comprehension. It is suggested that teachers of English apply Semantic Mapping StrategyÂ as one of the alternatives in teaching reading comprehension.